Estudio de las seguridades de las transacciones en línea en el ecuador, año 2022 - Ayme Paredes, Darwin Ariel (2023)
In today's globalization, the use of the Internet is very widespread, therefore, it is important to take into account that the transactions are made safely, and especially according to the current legislation in Ecuador. Online transactions of electronic commerce in Ecuador have had a great impact on the market; consumers make transactions of purchase and sale of products and / or services electronically with increasing frequency, however, it is important to identify, what is the drawback that occurs at the time of verifying whether this type of trade is totally safe. There are several factors that make online transactions vulnerable in terms of data security. To solve these problems, technologies such as payment gateways have been developed and implemented to provide security when making online transactions. The main objective of this research is to study the security of online transactions, due to the continuous crimes that exist in this regard. The descriptive research method was used, where the description of all the elements that are part of the process in electronic transactions through the Internet was made. The results show that the security features of payment gateways are made up of various protocols and security mechanisms, therefore, it is concluded that the use of these services guarantees efficiency, effectiveness and above all provides security to users.